2016
DOI: 10.5812/iji.42945
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii in Dairy Cattle and Camel in Sudan

Abstract: Background: Coxiella burnetii (C. burnetii) is the causative agent of Q fever, a zoonotic disease that is prevalent worldwide. Domestic and companion animals are the main reservoirs of infection. Humans mainly acquire the infection through inhalation of contaminated aerosols. Objectives: This study was carried out to detect the prevalence of C. burnetii antibodies in dairy cattle sera samples collected in nine states and in camel sera samples in four states in Sudan during May 2015-March 2016. Methods: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In the study by Klemmer et al the seroprevalence in camels from Aswan governorate bordering Sudan was 67.5%. This corroborates a study in Sudan that reported a seroprevalence of 64.3% (49/76) in camels and 29.9% in cattle (214). A recent study in Egypt reported that 4.5% (5/112) of camel sera were positive for anti-C. burnetii Ig, whereas a standard quantitative PCR found an overall prevalence of 15 to 19% (374).…”
Section: Camels: Another Animal Reservoir Of C Burnetii Besides Rumisupporting
confidence: 89%
See 1 more Smart Citation
“…In the study by Klemmer et al the seroprevalence in camels from Aswan governorate bordering Sudan was 67.5%. This corroborates a study in Sudan that reported a seroprevalence of 64.3% (49/76) in camels and 29.9% in cattle (214). A recent study in Egypt reported that 4.5% (5/112) of camel sera were positive for anti-C. burnetii Ig, whereas a standard quantitative PCR found an overall prevalence of 15 to 19% (374).…”
Section: Camels: Another Animal Reservoir Of C Burnetii Besides Rumisupporting
confidence: 89%
“…In Portugal, the frequency of exposure of ovine herds at C. burnetii seems to be increasing with possible impact on humans (212). On the African continent, a C. burnetii surveys of ovines indicated seroprevalences of 13% in Chad, 24% in Sudan, and 29% in Niger (105,213,214).…”
Section: The Main Known Reservoirs Of Coxiella Burnetii: Cattle Sheementioning
confidence: 99%
“…This prevalence is higher than the reported mean seroprevalence for C. burnetii in cattle in Africa, which currently stands at 14.0% while PCR detection was 9.0% [57]. On a similar note, a study conducted in some parts of Africa indicated different seropositivity to C. burnetii; as 29.9% was registered in dairy cattle in Sudan [62], and in Ethiopia, a seropositivity of 8.2% and 4.7% from semi-intensive and intensive management systems respectively was recorded [63]. Wardrop et al [61] reported an overall seroprevalence of 10.5% to C. burnetii in Western Kenya.…”
Section: Coxiella Burnetii Infection In Southern Nigeriamentioning
confidence: 58%
“…The prevalence of C. burnetii antibodies in camels and cattle sera samples collected from nine states was investigated in a study in 2015. The overall of 29.92% prevalence of C. burnetii antibodies was obtained although an overall of 64.5% prevalence rate was observed in camels ( 80 ).…”
Section: Resultsmentioning
confidence: 91%